Does Investment Opportunity Set, Financial Performance, and Dividend Policy Have An Influence on Sharia Stock Returns? - Nur Asmilia; Nindya Nur Meytta (El-Qish: Journal of Islamic Economics, 2023)
This research aims to examine the Investment Opportunity Set, Financial Performance, and Dividend Policy on Sharia Stock Returns. Empirical Study of Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange. The data used is secondary data and the method used is panel data analysis with the Eviews version 10 program to obtain a comprehensive picture of the relationship between one variable and another and the model used is the Fixed Effect Model (FEM) estimation. Sampling was carried out using purposive sampling technique. The sample selected based on the criteria was 16 (sixteen) companies with 5 years of research, so the total sample used in testing the research was 76 data. This research tests three independent variables, namely Investment Opportunity Set, Financial Performance, and Dividend Policy which has the dependent variable Stock Return. The results of this research in the partial test or t test show that the Investment Opportunity Set has an effect on Stock Returns, while Financial Performance and Dividend Policy have no effect on Sharia Stock Returns.